The potential habitat of Angelica dahurica in China under climate change scenario predicted by Maxent model - Zhang, Fen-Guo; Liang, Furong; Wu, Kefan; Xie, Liyuan; Zhao, Guanghua; Wang, Yongji (Frontiers in Plant Science, 2024)
Based on the geographical distribution of Angelica dahurica (A. dahurica) in China and 22 environmental factors, the MaxEnt model combined with the Geographic Information System (GIS)was used to predict the potential habitat of A. dahurica in China, which will provide an important reference for the utilization of A. dahurica resources and conservation. The results showed that: the mean value of the area under the ROC curve (AUC) was 0.879, and the TSS value was above 0.6, meaning that the MaxEnt model had a high accuracy in predicting the potential habitat area of A. dahurica; the effects of the five environmental variables, namely, bio6 (Min temperature of the coldest month), bio12 (Annual Precipitation), bio17 (Precipitation of Driest Quarter), elevation and slope, were relatively large. The cumulative contribution of the four factors reached 89.6%. In our country's habitat for Yunnan,